Behavior of the Total Electron Content over the Arctic and Antarctic sectors during several intense geomagnetic storms - Mansilla, Gustavo Adolfo (2019)
In this paper, the behavior of TEC at three stations located in the Arctic and Antarctic sectors during some intense geomagnetic storms in the period 2012–2016 is analyzed. The results show the opposite storm effects in the Arctic and Antarctic regions. Both the positive and negative TEC disturbances presented more fluctuations over the Arctic stations than over the Antarctic stations. Moreover, the positive TEC disturbances were more significant in winter. The negative disturbances were generally long-lasting, sometimes interrupted by short-duration positive disturbances. Overall, the increases and decreases in TEC can be mainly attributed to changes (i.e., increase and decreases in the O/N 2 ratio respectively) in the thermospheric composition, but prompt penetration electric field could be responsible for the initial TEC disturbances. The thermospheric circulation and the disturbance dynamo, which are maintained due to prolonged high-energy input at high latitudes, can also play important roles at the end of main phase and during recovery phase.